Trading forest carbon to promote the adoption of reduced impact logging - Smith, J.; Applegate, G. (Food and Agriculture Organization of the United Nations, 2002)
The Clean Development Mechanism (CDM) of the Kyoto Protocol raised the hopes of many, that payment for carbon sequestration services would provide a significant incentive for sustainable management practices in industrial forestry in tropical countries. Data to assess how realistic these hopes are, remain scant and high degree of uncertainty about CDM rules make assessment hazardous. The analysis in this paper focuses on the potential for using carbon trading to stimulate adoption of reduced impact logging (RIL)-based sustainable forest management. The result shows that: (i) expectations about the contribution carbon projects could make towards inducing sustainable timber harvesting should be scaled down; (ii) the cost-effectiveness of RIL-based SFM projects is likely to be highly-specific; (iii) RIL projects should be targeted to areas where timber volumes under RIL are similar to volumes under conventional logging with repeated harvesting at short intervals; (iv) pro-active measures could also be taken to expand the niche for RIL projects and reduce the risk of leakage and project failure; (v) CDM RIL projects should not be perceived as a silver bullet for inducing sustainable management and preventing forest degradation. (YS)